A multilayered valve leaflet promotes cell-laden collagen type I production and aortic valve hemodynamics. (May 2020) - Nachlas, Aline L.Y.; Li, Siyi; Streeter, Benjamin W.; De Jesus Morales, Kenneth J.; Sulejmani, Fatiesa; Madukauwa-David, David Immanuel; Bejleri, Donald; Sun, Wei; Yoganathan, Ajit P.; Davis, Michael E.
Abstract: Patients with aortic heart valve disease are limited to valve replacements that lack the ability to grow and remodel. This presents a major challenge for pediatric patients who require a valve capable of somatic growth and at a smaller size. A patient-specific heart valve capable of growth and remodeling while maintaining proper valve function would address this major issue. Here, we recreate the native valve leaflet structure composed of poly-ε-caprolactone (PCL) and cell-laden gelatin-methacrylate/poly (ethylene glycol) diacrylate (GelMA/PEGDA) hydrogels using 3D printing and molding, and then evaluate the ability of the multilayered scaffold to produce collagen matrix under physiological shear stress conditions. We also characterized the valve hemodynamics under aortic physiological flow conditions. The valve's fibrosa layer was replicated by 3D printing PCL in a circumferential direction similar to collagen alignment in the native leaflet, and GelMA/PEGDA sustained and promoted cell viability in the spongiosa/ventricularis layers. We found that collagen type I production can be increased in the multilayered scaffold when it is exposed to pulsatile shear stress conditions over static conditions. When the PCL component was mounted onto a valve ring and tested under physiological aortic valve conditions, the hemodynamics were comparable to commercially available valves. Our results demonstrate that a structurally representative valve leaflet can be generated using 3D printing and that the PCL layer of the leaflet can sustain proper valve function under physiological aortic valve conditions.